2007
DOI: 10.1159/000103114
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness and Risk of Cardiovascular Events in High-Risk Patients

Abstract: Background and Purpose: There is epidemiological evidence that increased carotid intima-media thickness (IMT) is a predictor of cardiovascular disease (CVD) events. However, the significance of carotid IMT in high-risk patients in whom risk factors are managed clinically has not been adequately investigated. The purpose of this study was to determine the usefulness of carotid IMT measurement in such patients. Methods: The study comprised 900 outpatients with cardiovascular risk factors or established atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…The present findings support the use of the IBS index to discover factors related to plaque vulnerability. In our follow-up study for carotid atherosclerosis [26], Yamagami et al [21] confirmed the association between a low IBS index and risk factors such as smoking and dyslipidemia and showed that increased blood IL-6 levels are related to a low IBS index, pointing to the role of inflammation in plaque vulnerability. The IBS index analysis may allow examination of the involvement of genetic factors and gene polymorphism in plaque instability; such involvement has rarely been examined but is undoubtedly important.…”
Section: Discussionsupporting
confidence: 56%
“…The present findings support the use of the IBS index to discover factors related to plaque vulnerability. In our follow-up study for carotid atherosclerosis [26], Yamagami et al [21] confirmed the association between a low IBS index and risk factors such as smoking and dyslipidemia and showed that increased blood IL-6 levels are related to a low IBS index, pointing to the role of inflammation in plaque vulnerability. The IBS index analysis may allow examination of the involvement of genetic factors and gene polymorphism in plaque instability; such involvement has rarely been examined but is undoubtedly important.…”
Section: Discussionsupporting
confidence: 56%
“…The IMT measured by B-mode sonography is an accepted marker of atherosclerosis [25,26,27]. For this reason, in the present study CCA IMT was measured by B-mode sonography, as an index of early atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for the recruitment of participants and the definitions of atherosclerotic risk factors have been described elsewhere. 6 In brief, subjects were enrolled if they had ≥1 vascular risk factors such as hypertension, diabetes mellitus, dyslipidemia, or a current smoking status or a history of cardiovascular disease. Patients with collagen disease, malignant disease, and chronic inflammatory disease were excluded.…”
Section: Subjectsmentioning
confidence: 99%